F. Nietzsche’s Doctrine of Perspectivism and the Problem of Truth - Mickevičius, Arūnas (Problemos, 1996)
The article discusses Nietzsche’s critical attitude towards logic, rational thinking, language, and cognition. It is argued that logic was perceived by him as imperative schematization, while rational thinking was seen as interpretation according to this scheme. Cognition, as an explanation of the world, is opposed by interpretation. Cognition, as a schematizing interpretation, was, for Nietzsche, in constant becoming, and was not oriented towards the universal, absolute, only truth, but towards a multitude of truths. According to Nietzsche, both in the logical cognition of the world and in language, through which this cognition unfolds what is encountered is not the truth itself but only mistakes, interpretations, and masks which cannot say anything as to what the world really is. In this respect, there is no correspondence between the world and cognition and there is, a fortiori, no true theory which could represent the true state of the world and the truth. Everything is just an interpretation. Knowledge of the world unfolds as the fatal error without approaching the truth, and it just remains an interpretation, a mask. All theories are nothing but interpretations in conflict with one another. Nietzsche’s position, which is represented by his doctrine of Perspectivism is termed in the article as radical scepticism. The article aims to show that Nietzsche’s radical scepticism is based on the preconceived primeval experience of the existence of truth that is not controlled by a scientific method. In the opinion of the author, the preconceived yet cognitively unattainable primeval experience of truth is the measure and norm for all cognition. It allows Nietzsche to take an extra-perspectival position and proclaim truth, which is related to cognition controlled by scientific method, “a type of error”. Taken more generally, cognition, which is in constant flow, is an indefinite and unlimited changing and unstable interplay of errors, interpretations, and masks, which enable one to approach truth, not because, as Nietzsche asserts, “there is no ‘truth’ whatsoever”, but because the preconceived primeval experience of the existence of truth is essentially not available to cognition.